2014
DOI: 10.3389/fncel.2014.00314
|View full text |Cite
|
Sign up to set email alerts
|

Rho family GTPases: key players in neuronal development, neuronal survival, and neurodegeneration

Abstract: The Rho family of GTPases belongs to the Ras superfamily of low molecular weight (∼21 kDa) guanine nucleotide binding proteins. The most extensively studied members are RhoA, Rac1, and Cdc42. In the last few decades, studies have demonstrated that Rho family GTPases are important regulatory molecules that link surface receptors to the organization of the actin and microtubule cytoskeletons. Indeed, Rho GTPases mediate many diverse critical cellular processes, such as gene transcription, cell–cell adhesion, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
268
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(278 citation statements)
references
References 138 publications
9
268
0
1
Order By: Relevance
“…RhoGTPases and their regulators, GTPase-activating proteins (GAPs) and guanine-exchange factors (GEFs), are critical mediators of dendritic arborization, spine morphogenesis, growth cone development, axon guidance [240][241][242][243][244][245] and neuronal survival 246 .…”
Section: Rhogtpase Regulationmentioning
confidence: 99%
“…RhoGTPases and their regulators, GTPase-activating proteins (GAPs) and guanine-exchange factors (GEFs), are critical mediators of dendritic arborization, spine morphogenesis, growth cone development, axon guidance [240][241][242][243][244][245] and neuronal survival 246 .…”
Section: Rhogtpase Regulationmentioning
confidence: 99%
“…Rac1-KO mice generated using a Nestin-Cre system exhibited impaired radial migration and axonogenesis in CGNs (Tahirovic et al, 2010). Furthermore, although a relatively large number of downstream molecules and putative disease-related pathways have been suggested to involve Rac signaling, the number of diseases in which involvement of Racassociated molecules/pathways has been established is quite low (Govek et al, 2005;Stankiewicz and Linseman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of cell cycle procedure was known to provide neuroprotection in other CNS injury models [32], along with reduced the release of microglial-associated inflammatory factors and glial scar formation [33]. Recently, it has been reported that LGR5 is known as a transmembrance receptor for increases canonical Wnt signaling amplitude.…”
Section: Discussionmentioning
confidence: 99%